PENGARUH KUALITAS PELAYANAN, FASILITAS DAN LOKASI TERHADAP KEPUTUSAN TAMU UNTUK MENGINAP DI HOTEL HARRIS WATERFRONT - Silaban, Leo Steven; Raymond (SCIENTIA JOURNAL, 2021)
This study aim to find the effect of service quality, facilities and location on the guest's decision to stay at the Harris Waterfront Hotel. Quantitative research is type of research with a population of 12,581 people. The data was collected using questionnaire and this study used the Slovin formula so that 100 samples. The data is process by SPSS 26 with the results quality of service t count > t table is 5.664 > 1.98498 with significance 0.000 < 0.05 that means service quality has positive and significant effect on stay decision, t count facilities > t table is 5.248 > 1.98498 with significance 0.000 t table is 2.736 > 1.98498 with a significance 0.007 <0.05, which means that location has positive and significant effect on stay decision. And the quality of service, facilities and location have a positive and significant effect on stay decision as proven by F test with a value of Fcount 100,503 > 2.70 Ftable with a significant 0.000 < 0.05 and its R Square value 0.751.